The K-12 Maker Studio: Towards Teaching and Development of Design Literacy in Educational Maker Settings - Hjorth, Mikkel (AU Library Scholarly Publishing Services, 2020)
This dissertation presents three years of research into the introduction of maker settings into formal education for students in Denmark aged 11– 15. The dissertation is concerned with design literacy as a possible path to prepare students for a world which is and will be radically changed by digital technologies. It is based on six publications: five papers and one report. In the dissertation, I provide an overview of my research, which has explored the possibilities of developing design literacy in the context of maker settings in formal education, guided by the following question: How can activities with maker technologies in formal educational settings contribute to the development of design literacy among adolescents? The answer to this question derives from observational and intervention studies in schools, a professional development course for teachers, two large-scale surveys, and post-project interviews with students. In total, three intertwined and overlapping research programs produced contributions to the emerging research field of making in education. This field explores the introduction of maker technologies (such as 3D printers and programmable electronics) and maker practices known from makerspaces to informal and formal education. The research presented here, contributes to the field of making in education in four perspectives: From a conceptual perspective, I have contributed to a turn towards design in the field of making in education by investigating design process knowledge, design judgment, and stance towards inquiry as aspects of design literacy. From a pedagogical perspective, I have studied the K-12 maker studio as an approach to teaching as well as teachers who implement such an approach. By unfolding challenges for teachers and development of competences, I have contributed to a focus on teachers in the field. From an assessment perspective, I have contributed knowledge on how to sustain and scale development of design literacy through K-12 maker settings by investigating tools for assessing larger-scale implementations of such maker settings in education. From an exemplar perspective, I have contributed exemplars of K-12 maker studio activities with in a design literacy perspective, of professional development of teachers, as well as of ways to research maker settings in education through such exemplars.